Using food aid to empower communities: concepts and examples from Madagascar and Honduras - Garrett, James L. (International Food Policy Research Institute, 2005)
...IFPRI examined the effectiveness of community-based targeting following three recent emergencies: the 1998 floods in Bangladesh; the 2002 drought in Ethiopia; and the 2001-02 failed maize harvest in Malawi.